2007
DOI: 10.1253/circj.71.1755
|View full text |Cite
|
Sign up to set email alerts
|

Higher Heart Rate Predicts the Risk of Developing Hypertension in a Normotensive Screened Cohort

Abstract: ypertension is the most prevalent disorder that affects a vast majority of adults in Japan and is an important risk factor for myocardial infarction and cerebrovascular disease. 1 Among the metabolic syndrome components, hypertension is the strongest predictor for cardiovascular events 2 or carotid atherosclerosis. 3 Moreover, high blood pressure (BP) is a useful predictor for excess medical costs. 4 Therefore, the prevention of hypertension is an important public health issue. Patients with prehypertension ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
6
25
0
Order By: Relevance
“…23 Moreover, a higher heart rate predicts the risk of developing hypertension in a normotensive screened cohort. 24,25 Cirrhosis is also associated with increased heart rate and blood pressure and heart rate obtained during the 24-h monitoring were positively and closely correlated. 26 Combination of cirrhosis and hypertension may have an additive effect on heart rate.…”
Section: Discussionmentioning
confidence: 94%
“…23 Moreover, a higher heart rate predicts the risk of developing hypertension in a normotensive screened cohort. 24,25 Cirrhosis is also associated with increased heart rate and blood pressure and heart rate obtained during the 24-h monitoring were positively and closely correlated. 26 Combination of cirrhosis and hypertension may have an additive effect on heart rate.…”
Section: Discussionmentioning
confidence: 94%
“…[20][21][22] Many patients with tachycardia have the characteristic features of insulin resistance syndrome, namely high blood pressure, obesity, increased blood glucose and insulin and an abnormal lipid profile. 7 Accordingly, it is likely that tachycardic patients are at a high risk for cardiovascular events 8,23 and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…28 In regard to Japanese, a study reported that HR was the strongest predictor of all-cause death among SBP and DBP, antihypertensive medication, HR, uric acid, VC, and serum cholesterol after adjustment for age. 29 Another epidemiological study in Japanese reported that a higher HR was independently associated with the development of hypertension in a logistic regression analysis adjusted for gender, age, alcohol consumption, exercise, atherosclerotic risk factors, and lifestyle. 30 Pathophysiological studies indicate that a relatively high HR has direct detrimental effects on the progression of coronary atherosclerosis, on the occurrence of myocardial ischemia and ventricular arrhythmias, and on left ventricular function.…”
Section: Discussionmentioning
confidence: 99%